Effects of acute noise stress on cognitive performance and lipid peroxidation among young male and female Wistar rats (African Journal of Biomedical Research, 2024)
Noise has been reported to have deleterious effect; this effect seems to be gender sensitive.  This study evaluated the effects of acute noise on cognitive performance in young females and males Wistar rats. Wistar rats weighing 70 to 120 g were randomly divided into four groups (n = 6). Group 1(Female experimental), Group 2 (Male experimental), Group 3 (Female control), and Group 4 (Male control).The experimental groups were exposed to noise  4 hours daily for 14 days consecutively, and their cognitive abilities tested on day 15.Vital samples; brain and serum were collected for biochemical and histological analysis. The homogenate was used to evaluate the concentration of malondialdehyde (MDA), while serum for corticosterone and H and E stains for cytoarchitectural changes. Mean differences were calculated using two-way analysis of variance (ANOVA) factors; sex and stress.  Discrimination index (DI) decreased in females, compared to males in the experimental groups. The mean values of corticosterone and MDA increased in females compared to males in the experimental and control groups.  Cytoarchitectural change was not pronounced. Acute noise exposure impaired cognitive functions in both young male and female Wistar rats and caused elevated levels of MDA, an indicator of lipid peroxidation. These findings suggested noise stress impaired cognition, and the impact may be more pronounced in female rats compared to males.